Synthesis Of Silica Nanocolloids Encapsulated Dyes For Bio-Imaging And Bio-Labeling Applications - Ahmad, Atiqah (2018)
Two different types of fluorescent dyes which are 1,1%-dioctadecyl 3,3,3%,3%-tetramethylindocarbocyanine perchlorate (DiI) and fluorescein (Fluo) were encapsulated inside the amorphous silica nanoparticles (SiNPs) using micelle entrapment method. 2-butanol which acted as a co-solvent to facilitate hydrolysis reaction during the synthesis process was varied in order to investigate the effect on the particle size. The synthesised samples were analysed and characterised to determine the hydrodynamic size of particles, average particle size and particles morphology, absorbance properties, fluorescence properties and crystallinity of the samples. Spherical and monodispersed nanoparticles (NPs) with different sizes ranging from 26.2 to 53.4nm, were obtained when synthesised using 2, 4 and 6 ml volume of co-solvent, 2-butanol respectively. The photostability effect between SiNPs encapsulated with Fluo dye (SiFluo) and SiNPs encapsulated with DiI dye (SiDiI) were conducted. SiDiI showed good photostability effect compared to SiFluo. Therefore, selected particle sizes of SiDiI 30.4, 40.0 and 53.4 nm were further analysed to study the particles stability in different biological medium (NaCl and mouse serum), cytotoxicity and fluorescent cell imaging in living cells, human breast adenocarcinoma (MCF-7). SiDiI with size 53.4 nm showed good photostability with only 11 % of decolourisation and obtained good particles stability in both NaCl solution and mouse serum. The cytotoxicity study showed that cytotoxicity of SiDiI is size dependent whereby SiDiI with size 53.4 nm was less toxic. Furthermore, bright and high contrast fluorescent cell images of MCF-7 treated with SiDiI with size 53.4 nm was observed.